Pengaruh Program Fast Read Terhadap Kemampuan Membaca Pemahaman Siswa Kelas III Sekolah Dasar - Rochmadona Stjawati; Muhamad Afandi (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
The Effect of FAST READ Program on Third Grade Students’ Reading Comprehension. This study was conducted to investigate the effect of the FAST READ program (Fun Active Strategy for Reading Efficiency and Development) on elementary students’ reading comprehension skills. A quantitative approach was employed using a quasi-experimental method with a one-group pretest–posttest design. The participants consisted of 27 third-grade students. Data were obtained through reading comprehension tests administered prior to and following the implementation of the treatment. The findings revealed an improvement in students’ mean scores, increasing from 73.50 in the pretest to 81.50 in the posttest. The paired sample t-test results showed a significance value below 0.05, indicating a statistically significant difference between the two measurements. Furthermore, the N-gain value of 0.19 was classified as low, suggesting a limited level of improvement. Overall, the implementation of the FAST READ program demonstrated a positive impact on students’ reading comprehension skills, although the magnitude of improvement remains relatively modest.